Physico-chemical properties, and water and oil uptake characteristics of novel, soy-based snacks processed using extrusion - Kodavali, Swathi Sree (Kansas State University, 2012)
Extrusion processing and frying are the two most commonly used methods to produce savory snacks. These snacks are mostly starch based and also contain high amounts of fat. Snacking percentage has increased drastically over the past few decades causing many health problems like obesity, hypertension and cardiovascular diseases. The overall objective of this study was to develop novel soy based savory snack that are high in protein and has less fat using both extrusion processing and frying. In the first part of this study both defatted soy (25-75%), wheat flour, monoglycerides (0.375 & 0.75%) and sodium bicarbonate (0 and 0.5%) were used to produce dense extrudates, which mimic the shape of lentils using pilot scale twin screw extruder. The extrudates were soaked in water and fried in corn oil to produced savory snacks. Soy influenced the water absorption during soaking and oil uptake during frying. The water uptake and % fat decreased with increase in soy and the amount of water uptake influenced the % fat absorption in the product. No significant differences were observed in overall acceptability and to summarize the increased protein and dense structure of the products challenge the texture of the products. In the second part of this research, dynamics of water and oil uptake were studied to see the role of texture modifiers like soy protein isolate (4, 8, & 12%), calcium bicarbonate (0.2, 0.4 & 0.6%) and pregelatinized wheat starch (4, 8, & 12%) on texture, water and oil uptake. Descriptive sensory analysis was conducted to study the sensory attributes of the products. Water holding capacity is influenced by the level of % starch addition and the degree of starch degradation during processing. Oil uptakes correlates to that of WHC and is also affected by the degree of gelatinization and crust formation. Degree of starch gelatinization, oil uptake and oil and starch matrix interactions had an impact on hardness. Among SPI, CaCO3 and PGWS, PGWS lowered the product hardness followed by SPI and CaCO3. Descriptive sensory results are similar to experimental results with PGWS samples having lower initial or substantial hardness and more oxidized or heated oil aroma and flavor.
Keywords: Extrusion; Savory snacks; Soy based snacks; Moisture and oil uptake; Frying; Sensory analysis; Food Science (0359); Nutrition (0570)